2014
DOI: 10.1097/aco.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Preventing and managing perioperative pulmonary complications following cardiac surgery

Abstract: Postoperative pulmonary complications are common, but severe complications are infrequent. Their reduction requires measures to prevent infection and mechanical ventilation-associated lung injury through the use of low tidal volumes and early extubation. Noninvasive ventilation after extubation can be utilized to avoid reintubation and the associated increased morbidity and mortality. However, noninvasive ventilation should be done under rigorous conditions and by following strict criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 61 publications
2
39
0
8
Order By: Relevance
“…There were 2 trials that investigated the relationship of different FiO 2 levels (FiO 2  = 0.21; 1.0) with the PaO 2 /FiO 2 [22,32] and they suggested that perioperative hyperoxia was potentially harmful by increasing the expression of reactive oxygen species and decreasing receptors in cells. [34] Considering the lung injury caused by high FiO 2 , we excluded the group that using 100% oxygen in those 2 trials.…”
Section: Discussionmentioning
confidence: 99%
“…There were 2 trials that investigated the relationship of different FiO 2 levels (FiO 2  = 0.21; 1.0) with the PaO 2 /FiO 2 [22,32] and they suggested that perioperative hyperoxia was potentially harmful by increasing the expression of reactive oxygen species and decreasing receptors in cells. [34] Considering the lung injury caused by high FiO 2 , we excluded the group that using 100% oxygen in those 2 trials.…”
Section: Discussionmentioning
confidence: 99%
“…As observed by García-Delgado et al (40) at any rate, strategies that are recommended to limit the effect of CPB on lung injury should include a reduction in CPB duration or the use of off-pump CABG, heparin-coated circuits, leucocyte depletion or intra-operative ultrafiltration. Since safety of restricted hemoglobin target (7-8 mg/dL) has been proved (41), minimization of blood product administration should be pursued to decrease the risk of TRALI.…”
Section: Preventive Measuresmentioning
confidence: 99%
“…The use of higher PEEP levels (10 cmH 2 O for the first 4 hours followed by PEEP levels of 5 cmH 2 O until tracheal extubation) improved pulmonary compliance and oxygenation compared to lower PEEP level (5 cmH The anesthetic technique significantly impacts on time to extubation, also. Early extubation, generally considered to be that which is performed during the first 6-8 hours once the preoperative homeostatic state has been reestablished (40), offers a substantial advantage in terms of accelerated recovery, shorter intensive care unit and hospital stay, suggesting that efforts to reduce extubation time are cost-effective (65). Cardiac surgical patients in whom low tidal volumes are administered are more likely to undergo early extubation (37.3% vs. 20.3%; P=0.02) and less likely to require re-intubation (1.3% vs. 9.5%; P=0.03) (66).…”
Section: Non-surgical Techniquesmentioning
confidence: 99%
“…Over recent years, several preventive lung-protective strategies have been investigated and proposed [6, 7]: ultrafiltration to remove neutrophils [8], controlled hemodilution (with a hematocrit higher than 23%), steroids [9] and adjusting MV settings during CPB, such as the application of positive end-expiratory pressure (PEEP) or continuous positive airway pressure (CPAP) of 5–15 cmH 2 O, low tidal-high frequency ventilation (100 acts/min), the application of 100% oxygen inspired fraction (FiO 2 ), and bilateral CPB which involves using the lungs for blood oxygenation [10]. …”
Section: Introductionmentioning
confidence: 99%